Consols, Financial Stability, and Pax Britannia - William O. Brown; Richard C. K. Burdekin; Marc D. Weidenmier (Claremont McKenna College, Department of Economics, 2004)
This paper identifies a sharp decline in the volatility of consol prices after the end of the Napoleonic wars in 1815. The volatility of consol returns drops by more than half after 1815 and our empirical testing confirms a long period of remarkable stability that includes the entire Victorian era at the height of Pax Britannia. Over our 1729-1959 sample period significant shifts in the consol series, reflecting military events and monetary and fiscal policy shifts, are concentrated in the period between the Seven Years? War and Waterloo. There are no outliers between 1816 and 1914.
Keywords: N2; H3; E6; 330; consols; British Empire; war; policy regimes; Öffentliche Anleihe; Volatilität; Politische Stabilität; Geschichte; Grossbritannien